Local and spatially extended sub-Poisson atom-number fluctuations in optical lattices - Gross, Christian; Estève, Jerome; Oberthaler, Markus K.; Martin, A. D.; Ruostekoski, J. (Physical review. A, Atomic, molecular, and optical physics, 2011)
We demonstrate that ultracold interacting bosonic atoms in an optical lattice with large on-site population show sub-Poisson on-site and intersite atom-number fluctuations. The experimental observations agree with numerical predictions of the truncated Wigner approximation. The correlations persist in the presence of multimode atom dynamics and even over large spatially extended samples involving several sites.
Gesehen am 18.07.2022